ACSL4-dependent ferroptosis does not represent a tumor-suppressive mechanism but ACSL4 rather promotes liver cancer progression - Julia Grube; Marius Maximilian Woitok; Antje Mohs; Stephanie Erschfeld; Celina Lynen; Christian Trautwein; Tobias Otto (Cell Death and Disease, 2022)
Abstract Ferroptosis is a novel type of programmed cell death that differs from apoptosis in that it involves iron-dependent peroxidation of membrane phospholipids. Its role in a variety of human disorders, including cancer has been hypothesized in recent years. While it may function as an endogenous tumor suppressor in a variety of cancers, its role during initiation and progression of liver cancer, particularly hepatocellular carcinoma (HCC), is yet unknown. Because HCC is most commonly found in chronically injured livers, we utilized two well-established mouse models of chronic injury-dependent HCC formation: Treatment with streptozotocin and high-fat diet as metabolic injury model, as well as treatment with diethylnitrosamine and carbon tetrachloride as toxic injury model. We used mice with hepatocyte-specific deletion of Acsl4, a key mediator of ferroptosis, to explore the significance of ferroptotic cell death in hepatocytes, the cell type of origin for HCC. Surprisingly, preventing ferroptotic cell death in hepatocytes by deleting Acsl4 does not increase the formation of HCC. Furthermore, Acsl4-deficient livers display less fibrosis and proliferation, especially in the HCC model of toxic damage. Intriguingly, in this model, the absence of ACSL4-dependent processes such as ferroptosis significantly slow down the growth of HCC. These findings suggest that during HCC formation in a chronically injured liver, ferroptotic cell death is not an endogenous tumor-suppressive mechanism. Instead, we find that ACSL4-dependent processes have an unanticipated cancer-promoting effect during HCC formation, which is most likely due to aggravated liver damage as demonstrated by increased hepatic fibrosis. Previous studies suggested that ferroptosis might have beneficial effects for patients during HCC therapy. As a result, during HCC progression and therapy, ferroptosis may have both cancer-promoting and cancer-inhibitory effects, respectively.